2015
DOI: 10.1186/s40064-015-1238-6
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of CCR5-Δ32, CCR2-64I and SDF1-3′A alleles in the Baiga and Gond tribes of Central India

Abstract: Human immunodeficiency virus-1 (HIV-1) which causes acquired immune deficiency syndrome (AIDS), by infecting CD4+ immune cells and hence weakening the host defense mechanism till death, is one of the major factor responsible for human demises worldwide. Both innate (monocytes and macrophages) and adaptive (T cells) immune cells expresses chemokines receptors (2 and 5) and stromal cell derived factor-1 (SDF-1) which play crucial role in HIV-1 virus entry and progression. Allele variants of genes CCR5 (CCR5-Δ32)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In the present study, the frequency of the CCR5Δ32 allele in healthy Turkmen people was not found. This is consistent with other studies from Iran [16,17,46,53,54] and other countries [55][56][57][58][59][60][61][62]. In contrast to our research, Trecarichi et al have shown a significantly higher frequency of Δ32 in the healthy control group compared to HIV-positive people.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the frequency of the CCR5Δ32 allele in healthy Turkmen people was not found. This is consistent with other studies from Iran [16,17,46,53,54] and other countries [55][56][57][58][59][60][61][62]. In contrast to our research, Trecarichi et al have shown a significantly higher frequency of Δ32 in the healthy control group compared to HIV-positive people.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies were reported at the context of disease epidemiology and genetics, upon various indian tribal communities, who are highly isolated both demographically and topogra phically, from the mainstream indian populations [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Among other African populations, frequencies ranging from 10%–30% have been reported. The frequencies of the CCR2-64I allele in African populations have been higher than what has been observed in Caucasians (7%–10%), while Asian populations show a wider range from 1%–30% 22. A study on subjects selected from different regions of Jordan showed that this allele is common among Jordanians, with a prevalence of 17.5% 8.…”
Section: Discussionmentioning
confidence: 88%